2021
DOI: 10.1186/s42409-021-00025-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring psychological pain: psychometric analysis of the Orbach and Mikulincer Mental Pain Scale

Abstract: Background Suicide is a public health concern, with an estimated 1 million individuals dying each year worldwide. Individual psychological pain is believed to be a contributing motivating factor. Therefore, establishing a psychometrically sound tool to adequately measure psychological pain is important. The Orbach and Mikulincer Mental Pain Scale (OMMP) has been proposed; however, previous psychometric analysis on the OMMP has not yielded a consistent scale structure, and the internal consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…Casanova et al did not evaluate OMMP-8 scale scores in predicting suicide risk and pointed to future studies. 12 In our study, the total score of the OMMP-8 scale successfully differentiated participants with and without suicide attempts in the depression group. The results suggest that the scale successfully predicts suicide risk, and its discrimination function is adequate.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Casanova et al did not evaluate OMMP-8 scale scores in predicting suicide risk and pointed to future studies. 12 In our study, the total score of the OMMP-8 scale successfully differentiated participants with and without suicide attempts in the depression group. The results suggest that the scale successfully predicts suicide risk, and its discrimination function is adequate.…”
Section: Discussionsupporting
confidence: 51%
“…Our study demonstrated that the Turkish version of the OMMP-8 scale fits the three-factor model well. The factors to which the items belong ( Figure 1 ) in our study are the same as Casanova et al Therefore, we named the factors in this study as Experience of Irreversibility (factor 1), Emotional Flooding (factor 2), and Narcissistic Wounds (factor 3) like Orbach et al and Casanova et al 12 , 13 Casanova et al found Cronbach’s alpha coefficient as 0.835 for “Experience of Irreversibility” subdimension, 0.856 for “Emotional Flooding”, and 0.767 for “Narcissistic Wounds” in the internal consistency analysis of the OMMP-8 scale. However, they reported that follow-up studies should support these data.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, Cronbach's alpha coefficient reported the subscales of this questionnaire between 0.75 and 0.95. 33,52 They said a Cronbach's alpha coefficient of 0.97 for the whole questionnaire and between 0.62 and 0.95 for the subscales. In a study by Karami et al ( 2018), the 6-factor model (emptiness, emotional flooding, loss of control, irreversibility, social distancing, and self-estrangement) was confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…Our systematic review identified 10 measures of mental pain developed over the past 20 years, mainly for the purpose of predicting suicide and used mostly in the field of clinical psychology. Some scales, such as the OMMPS, have shorter versions that we did not review independently 37. The 10 measures identified vary substantially in their theoretical frameworks, definitions of mental pain, semantics and content (poor content overlap and weak to very weak similarity).…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%